Dual antioxidant and cytotoxic activities of novel 1,2,3-triazole-decorated unsymmetrical monocarbonyl curcumin analogs - Bayu Ardiansah; Ahmad Farhan; Novita Sari Nurhasanah; Mochammad Arfin Fardiansyah Nasution; Noordini M. Salleh; Kenji Mizuguchi; Antonius Herry Cahyana; Lina Mardiana (Case Studies in Chemical and Environmental Engineering)
Unsymmetrical monocarbonyl curcumin analogs containing 1,2,3-triazole scaffold (5a-5f) have been synthesized from vanillin. 5d, which contains a carboxylic group, exhibited the highest antioxidant and cytotoxic activities, with an IC50 of 0.56 mM against DPPH and an IC50 of 38.25 ± 4.79 μM against MCF-7 cells. Docking studies revealed that 5d has high binding affinity for the tubulin protein, with predicted binding value of −10.4 kcal/mol. Additionally, in silico ADME predictions indicated that 5d demonstrates high gastrointestinal absorption and moderate intrinsic clearance. These findings indicate that the designed compounds, particularly compound 5d, could be promising for developing a new drug candidate.